Abnormal ratio of CD57+ cells to CD56+ cells in women with recurrent implantation failure. (20th May 2017) - Jiang, Ruiwei; Yan, Guijun; Xing, Jun; Wang, Zhilong; Liu, Yong; Wu, Hongyan; Fan, Xiangshan; Zhou, Jianjun; Ding, Lijun; Sun, Haixiang
Abstract : Problem: To define a more precise parameter for a better understanding of natural killer (NK) cells and its relation with regulatory T cells (Tregs) in women with recurrent implantation failure (RIF). Method of study: The percentages of CD56+ cells, CD57+ cells and Foxp3+ cells in the endometrium and blood from 23 normal controls and 32 women with RIF were measured by immunocytochemistry and flow cytometry. Results: Women with RIF had significantly increased ratio of CD57+ cells to CD56+ cells in both the endometrium ( P <.01) and blood ( P <.05), and decreased percentage of Foxp3+ cells in the endometrium ( P <.05). There was a significant negative correlation between CD57+ cells to CD56+ cells ratio and the percentage of Foxp3+ cells in the blood of RIF patients ( P <.05). Conclusion: Our study provides a novel assessment parameter, CD57+ cells to CD56+ cells ratio, to evaluate NK cells and its relation with Tregs in RIF patients.